Job satisfaction as a moderator between organizational culture and turnover intention among Malaysian police officers - Erny Yusnida Che Yusoff; Mohd Nasir Selamat; Rusyda Helma Mohd (PLoS ONE, 2025)
Turnover among police officers poses a serious challenge to law enforcement agencies by affecting operational stability and public trust. While organizational culture and job satisfaction are key factors influencing turnover intention, their combined effects have not been widely studied in policing contexts. This study explores whether job satisfaction moderates the relationship between organizational culture and turnover intention among Malaysian police officers. Although both variables were significantly related to turnover intention, the moderation effect of job satisfaction was not statistically significant. A cross-sectional survey was conducted among 373 officers from various departments of the Royal Malaysia Police. Participants completed validated instruments measuring organizational culture, job satisfaction, and turnover intention. Data were analysed using Hayes’ PROCESS Macro (Model 1) in SPSS to test for moderation effects through hierarchical regression. The analysis revealed that both organizational culture and job satisfaction were significantly and negatively associated with turnover intention, indicating that higher levels of these variables correspond to lower intentions to leave the organization. Officers who perceived stronger organizational culture and reported higher job satisfaction were less likely to express intent to leave. However, job satisfaction did not significantly moderate the relationship between organizational culture and turnover intention (p = .117), indicating that the influence of organizational culture on turnover intention remained stable regardless of satisfaction levels. The findings highlight the importance of fostering a supportive organizational culture to reduce turnover intention among police officers. While job satisfaction independently contributes to retention, it does not significantly alter the impact of organizational culture. These results suggest that efforts to improve retention in policing should focus on structural and cultural reforms in addition to enhancing job satisfaction.